DEVELOPING DIFFERENTIATED ELECTRONIC SUPPLEMENTARY READING EXERCISE FOR THE SLOW LEARNERS OF SEVENTH YEAR STUDENTS AT SMP N 2 SINGARAJA - K.A.A., Dinata; P.K., Nitiasih; N.W.S., Mahayanti (International Journal of Language and Literature, 2019)
Self-regulated learning (SRL) becomes one of the crucial skill in nowadays era. The ability to regulate their own learning, helps students to achieve better. In order to prove that, this study aimed at investigate the correlation between SRL strategies and the student’s English achievement by using expost facto research design. 152 students were involved to be the sample of this study and asked to fill Motivated Strategies for Learning Questionnaire (MSLQ) developed by Pintrich (1991) as the data of their SRL strategies. For the achievement, the record keeping document were used. As the result, it was found that there is a significant correlation between SRL strategies and the student’s English achievement.